2017
DOI: 10.1080/1406099x.2017.1318000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population ageing on the pension system in Belarus

Abstract: Belarus currently has a relatively generous pay-as-you-go pension system, but population aging coupled with recent problems with economic growth will soon make it unsustainable. We build a rich overlapping generation model of Belarusian economy, which shows that without reform the Pension Fund will run into persistent and growing deficit, which will reach 9% of GDP by 2055. We also compute the fiscal projections of several parametric pension reforms, including the reform which will start in 2017. To avoid a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This was due to low birth rates and survival rates for the 1940-1946 cohorts, resulting in low numbers of pensioners in recent years (Zviniene and Biletsky, 2011). While similar in size to other European countries (total pensions in Belarus were about 9 percent of GDP in 2013), a couple of characteristics are notable, including: (i) very low retirement ages (60 for men and 55 for women); (ii) very high contribution rates --total pension contributions are 29 percent of gross wages, of which 1 percent is paid by the employee and the rest is covered by the employer (Lisenkova and Bornukova, 2015).…”
Section: Contributions Of Pensions To Shared Prosperitymentioning
confidence: 84%
See 2 more Smart Citations
“…This was due to low birth rates and survival rates for the 1940-1946 cohorts, resulting in low numbers of pensioners in recent years (Zviniene and Biletsky, 2011). While similar in size to other European countries (total pensions in Belarus were about 9 percent of GDP in 2013), a couple of characteristics are notable, including: (i) very low retirement ages (60 for men and 55 for women); (ii) very high contribution rates --total pension contributions are 29 percent of gross wages, of which 1 percent is paid by the employee and the rest is covered by the employer (Lisenkova and Bornukova, 2015).…”
Section: Contributions Of Pensions To Shared Prosperitymentioning
confidence: 84%
“…The share of 60+ population in Belarus is projected to increase from 15 percent in 2000 to 35 percent in 2050, while the old age dependency ratio is projected to increase from 20 percent in 2000 to 46 percent in 2050. As the result of the shrinking working age population, and the increase in the share of elderly in Belarus, the projected fiscal flows in the pensions system in Belarus are projected to deteriorate, and the pension fund deficit could reach an equivalent of 9 percent of GDP by 2050 (Bornukova et al, 2015). The share of pension recipients both in the B40 population and in the T60 population increased between 2003 and 2015, and will continue increasing in the future, such future pension dynamics will play an increasingly important role in overall disposable income growth.…”
Section: Some Emerging Challenges To Future Shared Prosperitymentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has studied the impacts of these reforms on pension sustainability. For instance, by building a rich overlapping generation model, Lisenkova and Bornukova investigated Belarus' 2017 retirement reform [25]. They concluded that decreasing the pension replacement rate from 43% in 2013 to 28% in 2050 would help to keep the pension deficit below 3% of GDP in 2050, and the pension deficit would almost disappear in 2100.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This trend is due to retirement by baby boomers which affects towards the increment of elderly share population of the countries [4]. Consequently, the ageing population has the impacts on future productivity as well as economic growth of the country [5], [6].…”
Section: Introductionmentioning
confidence: 99%